Pengaruh Pendidikan Kesehatan Tentang Gizi Balita di Kelurahan Batin Tikal Kecamatan Tamansari Kota Pangkalpinang Kep. Bangka Belitung - Zone Asia Alva Berty; Vistra Veftisia (Universitas Ngudi Waluyo, 2025)
Community is a group of people who have at least one characteristic in common such as geography, occupation, ethnicity, interests and others. Toddler nutritional status is the nutritional condition of children under the age of five years which is assessed based on anthropometric indices (weight for age, height for age, and weight for height). Good nutritional status is very important for the growth and development of children, because poor nutritional status can cause various health problems such as stunting and malnutrition. The participants in this counseling activity were 11 mothers of toddlers. The activity was carried out by providing an explanation of the purpose of the activity, distributing pre-tests to target mothers of toddlers, providing health counseling on